Review of James Alfred Loader "Proverbs 1–9" (Historical Commentary on the Old Testament), Peeters Leuven, 2014 - Venter, Pieter (HTS teologiese studies, 2016)
Loader’s commentary on Proverbs 1–9 belongs to the category of technical commentaries. It is evaluated in terms of similar commentaries written by scholars who focus on interpreting the original Hebrew text. The design of the commentary, the four essays included in the commentary, and the approach to the text is discussed. A final section deals with Loader’s exposition of Proverbs 8. This section focuses on the problematic Hebrew terms qnh in 8:22 and ‘amon in 8:30 and compares his interpretation with the opinions raised by other scholars in this regard.